Developing and testing a measure for the corporate ethical identity of Shariah compliant organizations \ Roshima Said ... [et al.] - Said, Roshima; Mohd Sidek, Noor Zahirah; Omar, Normah (2019)
Malaysia’s aspiration to persist as the leader of the Islamic Capital Market entails its Shari’ah compliant organizations to embrace Islamic Business Ethics and values in an attempt to win the trust and confidence of its Muslim investors and stakeholders, by portraying their sincerity and earnestness in complying with Islamic values. Through promotion of extensive transparency and accountability will enable Malaysia to set up a comprehensive accounting, tax and regulatory framework to reinforce further its objectives as the champion of the Islamic Capital Market. Malaysia is facing an ever increasing competition from other Asia Pacific countries (such as Thailand, Philippines, Brunei and Singapore) and other Islamic Countries (such as Pakistan, Turkey and Bangladesh), that are trying to benefit from growing halal market. Accordingly, it is seen only natural that the government of Malaysia should ascend to deliberate on practicing Islamic Business Ethics on these Shari’ah compliant organizations as a niche area, if it wants to uphold and to seize the increasing trade with the Organization of Islamic Countries (OIC) in general and with GCC countries particularly.